The Role Of 'Aisyiyah City of Tasikmalaya in Social Services, Education and Community Health - Sunanih Sunanih; Budi Hendrawan; Sharah Febrian (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2022)
The development of 'Aisyiyah as a Muhammadiyah women's organization in West Java, especially Tasikmalaya, cannot be separated from the efforts and active role of the missionary since its inception in 1935 until now as Ahmad Dahlan hopes in encouraging women to pursue education, both in general and religious formal education. The struggle and movement of 'Aisyiyah are continuously carried out to benefit the community. This is due to the many problems faced by women and their families in various aspects of life. Asyiyah activities can be classified as community social service activities. The 'Aisyiyah movement in social services does not view 'money' as a goal, but rather gives benefits and wants to get the pleasure of Allah SWT. According to Suparlan,